In-Vitro study of the Anticoagulant Property of Terminalia Catappa (Talisay) Leaf Extract Using Gallus Gallus (Chicken) Blood - Vandon T. Borela; Klim Angelo L. Balunsat; Alyssa Juliana L. Briones; Patricia Nicole P. Briones (Journal La Lifesci, 2020)
Prothrombin time is a test used to help detect and diagnose a bleeding disorder or excessive clotting disorder. It is important to know the prothrombin time because it checks to see if five different blood clotting factors are present. Lack of Vitamin K and having Liver problems are one of the factors that can decrease the prothrombin time of the blood. This research aims to investigate the potential ability of the Terminalia catappa (Talisay) leaf extract to increases prothrombin time of chicken’s blood. The research methods used by the researchers is experimental. A research design where the results are being observed and determined when the independent variable took effect on the dependent variable. . The materials used are ethanol, calcium chloride, leaves and chicken blood. The method that was used in the study is in-vitro, a process that is performed in a test tube, or elsewhere outside a living organism. The 0.5 ml plasma sample was separated into four tubes and the first group of plasma was tested first to determine the initial prothrombin time while the other three groups with the different volumes of plant extract (0.2, 0.4, 0.6 mg/ml) was added separately. The tubes were tilted at about 45° until the permanent clots was obtained. These are recorded as the prothrombin time. The research showed that the Terminalia Catappa leaf extract is effective on increasing the normal prothrombin time of the blood.